Fever of unknown origin: A 12-year case series in Colombia - Vásquez-Jiménez, Juan Manuel; Mackenzie, Sebastián; Pulido-Arenas, Jorge; Bernal-Macías, Santiago; Garzon, Javier Ricardo; Ordóñez, Ivonne Tatiana; Correa, Néstor Fabián; Muñoz, Oscar (The Journal of Infection in Developing Countries, 2024)
Background: Fever of unknown origin (FUO) is a diagnostic challenge with highly heterogeneous causes. Its etiology can change according to the studied regions, and the chance of reaching a diagnosis depends on available resources. The aim of this study is to describe the clinical characteristics, etiology and the usefulness of diagnostic aids in cases of FUO managed over 12 years in a Colombian reference center. Methodology: Single-institution retrospective case series. All cases of FUO between 2006 and 2017 were identified with the help of an electronic medical record search software. Cases of adults with fever for more than three weeks who remained undiagnosed after three days of hospitalization are described. Results: Of 1,009 cases evaluated, 112 cases met the inclusion criteria (median age 43 years, 66% men). The etiologies identified were infectious (31.2%), inflammatory (20.5%), neoplastic (14.3%), and miscellaneous (2.7%) diseases. 31.2% remained without etiological diagnosis. The most frequent conditions were tuberculosis (17%), Hodgkin's lymphoma (7.1%), systemic lupus erythematosus (6.3%), disseminated histoplasmosis, and adult Still's disease. Contrast tomography and biopsies were the studies that most frequently supported or confirmed the final diagnosis. Conclusions: This series of contemporary Latin American cases suggests that the categories of FUO etiologies are similar to those reported in studies from developed countries, with tuberculosis being the most frequent cause in our setting. Our results highlight the importance of tomography-guided invasive studies in the diagnostic approach to FUO.